2016
DOI: 10.1245/s10434-016-5686-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreduction (Peritonectomy Procedures) Combined with Hyperthermic Intraperitoneal Chemotherapy (HIPEC) in Advanced Ovarian Cancer: Retrospective Italian Multicenter Observational Study of 511 Cases

Abstract: PurposeThe aim of this study was to help with the process of selecting patients with advanced ovarian cancer to undergo cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) by analyzing outcome data at distinct clinical time points reflecting the natural history of the disease.MethodsIn a retrospective Italian multicenter study investigating patients with advanced ovarian cancer who underwent CRS plus HIPEC between 1998 and 2014, we analyzed data for consecutive patients at eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 50 publications
6
77
1
Order By: Relevance
“…TPP thus ensures to remove all diseased tissue and limits any marginal miss that can happen from cytoreduction in PSM. However, the benefits of TPP in patients undergoing HIPEC has been explored only in few studies [3,9,10] and it has been underutilized due to concerns of associated morbidity [10]. Retrospective analysis of peritonectomy procedures in patients undergoing HIPEC for mesothelioma by Baratti et al [9] showed that TPP group had better OS with similar morbidity rates and was recognized as an independent predictor of better prognosis at multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPP thus ensures to remove all diseased tissue and limits any marginal miss that can happen from cytoreduction in PSM. However, the benefits of TPP in patients undergoing HIPEC has been explored only in few studies [3,9,10] and it has been underutilized due to concerns of associated morbidity [10]. Retrospective analysis of peritonectomy procedures in patients undergoing HIPEC for mesothelioma by Baratti et al [9] showed that TPP group had better OS with similar morbidity rates and was recognized as an independent predictor of better prognosis at multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It comprises of complete removal of macroscopic disease, so as to achieve a minimal residual disease of less than 2.5 mm 2 . Completeness of cytoreduction score (CC Score) has been found to be an important predictor of long term outcome after CRS in PSM of colorectal origin [2], ovary [3] and pseudomyxoma peritonei (PMP) [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a more recent study conducted by an Italian study group, conflicting results have been reported; contrarily to the French study, the Italian one came to demonstrate the efficacy of HIPEC exclusively in treating chemosensitive relapse from ovarian cancer; in the meantime, no clear benefit in terms of survival could be demonstrated for cases presenting resistant to platinum disease (16). Moreover, other studies excluded from the very beginning patients with platinum resistant disease from their study groups which aimed to investigate the effectiveness of HIPEC in recurrent ovarian cancer (17).…”
Section: Studies Investigating the Efficacy Of Hipec In Platinum Resimentioning
confidence: 98%
“…At a median followup of 53.8 months overall survival was 54.2 months (95% CI 44-58.4) and PFS was 16.6 months (95%, CI 14.7-19.1). 65 …”
Section: Hyperthermic Intraperitoneal Chemotherapy Early Postoperatimentioning
confidence: 99%